Politics and constitution-making in India and Pakistan - Barua, B. P., 1936- (New Delhi : Deep & Deep, 1984)
Study covers the period, 1919-1956.
Includes index.
Bibliography: p. [201]-213.
Keywords: Political planning -- India -- History; Political planning -- Pakistan -- History